2010
DOI: 10.1149/1.3368787
|View full text |Cite
|
Sign up to set email alerts
|

Catalysts with Pt Surface Coating by Atomic Layer Deposition for Solid Oxide Fuel Cells

Abstract: We tested the atomic layer deposition of platinum layers onto various sputtered porous metals including silver, palladium, ruthenium, and gold as catalysts for solid oxide fuel cells. We investigated thermal and chemical stability against oxidation using X-ray photoelectron spectroscopy. Fuel cell tests were conducted using the metal-atomic layer deposition platinum cathodes with 200 m thick, 8% yttria-stabilized zirconia electrolytes and sputtered platinum anodes. Performance of the fuel cells was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 33 publications
4
41
0
Order By: Relevance
“…15 These studies revealed that Pt ALD films thinner than 18.3 nm were discontinuous and porous. 21 Various degrees of Pt coverage on the different metals were observed that correlated with expectations from relative surface energies. Additional studies by the same group also observed that 72 cycles of thermal Pt ALD on various sputtered metals resulted in Pt clusters.…”
Section: A Previous Results For Pt Ald On Various Surfacessupporting
confidence: 55%
See 1 more Smart Citation
“…15 These studies revealed that Pt ALD films thinner than 18.3 nm were discontinuous and porous. 21 Various degrees of Pt coverage on the different metals were observed that correlated with expectations from relative surface energies. Additional studies by the same group also observed that 72 cycles of thermal Pt ALD on various sputtered metals resulted in Pt clusters.…”
Section: A Previous Results For Pt Ald On Various Surfacessupporting
confidence: 55%
“…9,10 Recent research has suggested that ultrathin conformal Pt films on a high surface area support will exhibit significantly higher area-specific activity for the oxygen reduction reaction than an equivalent surface area of Pt nanoparticles. [13][14][15][16][17][18][19][20][21] However, this Pt ALD chemistry does not yield continuous and conformal films as is typical for ALD film growth. Electronic mail: steven.george@colorado.edu.…”
mentioning
confidence: 99%
“…Atomic layer deposition (ALD) is a modified version of metalorganic chemical vapor deposition, which relies on the selflimiting chemistry of precursors and the interaction between substrates and precursor molecules [1,2]. Because it offers an atomic level control of thin-film growth using sequential and self-limiting surface reactions, the ALD process can be extensively used to deposit conformal films inside high aspect ratio structures.…”
Section: Introductionmentioning
confidence: 99%
“…Here we demonstrate, for the first time, the establishment of conformal mesoporous nanoionics ZrO 2 networks on the interior surface of porous commercial SOFC cathode formed through atomic layer deposition (ALD)2930313233. By contrast to the PLD thin film deposition and chemical solution based infiltration343536, chemical vapor based ALD is uniquely suitable for depositing uniform and conformal films on SOFC cathodes possessing complex three-dimensional topographies with high aspect ratio.…”
mentioning
confidence: 97%